Actio pauliana and international jurisdiction - Jiménez Gómez, Briseida Sofía (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
The Court of Justice has established a broad concept of what should be understood by “matters related to a contract” for the application of the Brussels I Regulation (Recast) Regulation. It has pronounced for the first time subsuming the litigation of the actio pauliana within the special forum of article 7(1) (a) of the Brussels I bis Regulation. However, it should be considered that the grounds used contradict part of its prior jurisprudence, undermining as a consequence the objectives of predictability and legal certainty.